Phytochemical Studies Of Mangrove Fruit (Rhizophora mucronata) From Langge Village, North Gorontalo District - Mile, Lukman; Nursyam, Happy; Setijawati, Dwi; Sulistiyati, Titik Dwi (Jambura Fish Processing Journal, 2021)
Mangroves are one of the beneficial plants that directly touch human life, especially coastal communities. The extract and raw materials from these mangroves are widely used as a source of food and for natural medicinal. The purpose of this study was to identify the chemical content and bioactive compounds of Rhizophora mucronata from Langge Village, Kecamatan Anggrek, North Gorontalo District. In this research, the research method used is descriptive method. To obtain the extract using the maceration method with methanol as a solvent. Chemical testing includes testing of moisture content, ash content, total fat, protein, carbohydrates, while the identification of bioactive compounds uses qualitative methods. The results of the chemical content test for water content of 52.38%; Ash content 0.22%; Total fat content 2.33%; protein content of 6.85% and carbohydrates 30.30% and the identified bioactive compounds are flavonoids, saponins, tannins, tripertenoids and steroids as well as phenol hydroquinone compounds.